2015
DOI: 10.1016/j.jpeds.2014.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Growth and the Development of Preschool Wheeze, Independent from Overweight: The LucKi Birth Cohort Study

Abstract: Only height growth rate, and not weight and BMI growth rate, is associated with preschool wheeze, independent of overweight. Children who wheeze demonstrate a subsequent reduction in height growth up to age 14 months, but not vice versa. Because height growth rate is not associated with overweight, preschool wheeze and overweight are not associated throughout early life growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Our results displayed the there was no statistical significance among the infants with normal weight, low weight and overweight. It is indicated that the occurrence of wheezing is not relevant to weight [27], but may be associated with growth speed, which is in accordance with previous reports [10, 28, 29]. Evidences demonstrated that the weight growth speed might serve as a potential influencing factor in obesity [19], pulmonary function decline [29], bronchial asthma [30], cardiovascular disease [16], and type 1 diabetes [17] during infancy.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our results displayed the there was no statistical significance among the infants with normal weight, low weight and overweight. It is indicated that the occurrence of wheezing is not relevant to weight [27], but may be associated with growth speed, which is in accordance with previous reports [10, 28, 29]. Evidences demonstrated that the weight growth speed might serve as a potential influencing factor in obesity [19], pulmonary function decline [29], bronchial asthma [30], cardiovascular disease [16], and type 1 diabetes [17] during infancy.…”
Section: Discussionsupporting
confidence: 77%
“…Studies found that nearly half of children had wheezing within 1 year after birth, especially no more than 6 months [4]. To date scholars mostly had focused on investigating the effects of weight gain on wheezing or recurrent wheezing in different periods [12, 2326], meanwhile several researchers found that growth speed was a risk factor for respiratory disease among children [27]. Our results displayed the there was no statistical significance among the infants with normal weight, low weight and overweight.…”
Section: Discussionmentioning
confidence: 99%
“… 19 21–23 In addition to that, all of these studies, with the exception of one, 18 assumed homogeneous growth among children, either used statistical techniques that can now be improved on or a non-standard growth data analysis that makes comparison and replication of results very difficult. For example, three 11 16 20 used data-driven standardised scores (SDS), three 12 19 22 23 used country-specific SDS and another one 14 used non-standardised weight measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies addressing this issue were based on rather simple growth modelling,3 5 6 8 12 14 15 evaluating the difference in two growth measurements, usually expressed as change in weight/weight for length or body mass index (BMI) SD z scores. Some other studies used more complex growth models considering different patterns of early growth trajectories 4 7 9 10 11 13 16.…”
Section: Introductionmentioning
confidence: 99%